2014
DOI: 10.1021/ml500002n
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of BI 224436, a Noncatalytic Site Integrase Inhibitor (NCINI) of HIV-1

Abstract: An assay recapitulating the 3′ processing activity of HIV-1 integrase (IN) was used to screen the Boehringer Ingelheim compound collection. Hit-to-lead and lead optimization beginning with compound 1 established the importance of the C3 and C4 substituent to antiviral potency against viruses with different aa124/ aa125 variants of IN. The importance of the C7 position on the serum shifted potency was established. Introduction of a quinoline substituent at the C4 position provided a balance of potency and metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
167
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(177 citation statements)
references
References 23 publications
8
167
1
Order By: Relevance
“…The initial hit from the NCINI series was identified using a fluorescence-based assay with an LTR DNA probe to measure the 3=-processing enzymatic activity of HIV-1 integrase. Medicinal chemistry optimization combined with rational design based on our understanding of the binding mode of our inhibitors led to the identification of our first development candidate, BI 224436 (18). A mean IC 50 of 15 Ϯ 4 nM was obtained for BI 224436 with the LTR 3=-processing assay (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial hit from the NCINI series was identified using a fluorescence-based assay with an LTR DNA probe to measure the 3=-processing enzymatic activity of HIV-1 integrase. Medicinal chemistry optimization combined with rational design based on our understanding of the binding mode of our inhibitors led to the identification of our first development candidate, BI 224436 (18). A mean IC 50 of 15 Ϯ 4 nM was obtained for BI 224436 with the LTR 3=-processing assay (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using an integrase LTR DNA 3=-processing assay in a highthroughput format, we identified a 3-quinolineacetic acid series that specifically inhibited the 3=-processing step catalyzed by integrase (18,19). After preliminary optimization in hit-to-lead chemistry, biochemical assays showed that in addition to inhibiting the 3=-processing step, this series also inhibited the LTR DNA interaction with integrase and the interaction between integrase and LEDGF without inhibiting the strand transfer activity of integrase (S. Mason and C. Fenwick, unpublished data).…”
mentioning
confidence: 99%
“…[33][34][35][36]. These compounds bind at the IN CCD dimer interface occupying the principal LEDGF/p75 binding pocket (12,(37)(38)(39)(40)(41)(42).…”
Section: Hiv-1 Integrase (In)mentioning
confidence: 99%
“…In these particles, the viral ribonucleoprotein complexes (vRNPs), mainly composed of the viral genomic RNA and NC, are eccentrically localized between the empty CA lattice and the viral membrane (7,9,17). A remarkably similar morphological defect is observed in particles generated in the presence of allosteric integrase inhibitors (ALLINIs) (also known as LEDGINs, NCINIs, or INLAIs) (18)(19)(20)(21)(22)(23). Proposed mechanisms that underlie this morphogenesis defect include ALLINI-induced aberrant IN multimerization (9,17,(24)(25)(26)(27) and inhibition of IN binding to the viral RNA genome (4).…”
mentioning
confidence: 96%